Impact of Patient Safety Incidents Reported by the General Public in Korea. Issue 8 (December 2021) - Pyo, Jeehee; Lee, Won; Jang, Seung Gyeong; Choi, Eun Young; Ock, Minsu; Lee, Sang-Il
Abstract : Objective: The study aimed to investigate the impacts of patient safety incident (PSI) experienced by the general public. Methods: We conducted a self-administered online survey, in which we examined the following experiences of the patients and the caregivers: the level of harm induced by PSIs, difficulties due to PSIs, posttraumatic stress disorder (PTSD), and posttraumatic embitterment disorder, etc. A χ 2 test was performed to identify differences in difficulties because of the direct and indirect experience of PSIs. A 1-way analysis of variance was performed to identify the differences in the total PTSD and posttraumatic embitterment disorder scores according to the characteristics of PSIs. Results: Of the survey participants who indirectly experienced PSIs, 27.2% and 29.3% reported that they experienced sleep disorder and eating disorder, respectively. However, of the participants who directly experienced PSIs, 40.7% and 42.6% reported experiencing sleep disorder and eating disorder, respectively. The average PTSD scores of the participants who experienced permanent disability and death were 83.8 points for less than 6 months of elapsed time since the incident, 80.8 points for 6 months to less than 5 years, and 94.7 points for 5 years or more; they did not demonstrate a statistically significant difference ( P = 0.217). Conclusions: This study suggested that the general public who experienced PSIs have numerous difficulties at the time of the incident and the trauma or the resentment of the general public does not quickly regress even if time passes. Abstract : Supplemental digital content is available in the text.